Developing a Madrasah Culture-Based Etiquette Education Model: A Case Study of Darut Tauhid Islamic Primary School, Jember, Indonesia - Karimah, Sa'idah; Ningsih, Erlin Indaya (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to develop a madrasah culture-based etiquette education model in strengthening students’ character in Islamic primary education. The study is grounded in the concern that etiquette education in madrasahs is often implemented in a fragmented and unsystematic manner, limiting its effectiveness in fostering students’ moral development. Therefore, this research seeks to analyze the existing practices of etiquette education and to formulate a more integrated and sustainable model based on madrasah culture. This study employs a qualitative approach using a case study design conducted at Darut Tauhid Islamic Primary School, Jember, Indonesia. Data were collected through observations, in-depth interviews, and document analysis involving school leaders, teachers, and educational staff. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing, while ensuring trustworthiness through triangulation and validation techniques. The findings reveal that etiquette education has been implemented through habituation practices, religious activities, and teacher role modeling, supported by subjects such as Akhlaqul Lil Banin and Aqidah Akhlak. However, its implementation remains partially structured, lacking systematic integration across the curriculum and consistency in practice. Despite these limitations, the study shows that such practices have a significant positive impact on students’ discipline, politeness, and social responsibility. Based on these findings, the study proposes an integrative model consisting of five key components: Islamic value foundation, teacher exemplarity, integrated habituation, supportive madrasah environment, and parental collaboration. The novelty of this study lies in its effort to conceptualize etiquette education not merely as a set of habitual practices, but as an integrated system embedded within madrasah culture. It also offers a contextual application of the concept of adab in Islamic primary education, bridging theoretical perspectives with practical implementation. This study contributes to the field of Islamic education by providing a conceptual framework that integrates character education theories with Islamic values, while also offering practical guidance for developing more structured and sustainable etiquette education programs in madrasahs. The findings are expected to support educators and policymakers in strengthening value-based education within Islamic schooling contexts.